2016
DOI: 10.1530/eje-15-0860
|View full text |Cite
|
Sign up to set email alerts
|

Compromised cortical bone compartment in type 2 diabetes mellitus patients with microvascular disease

Abstract: Objective and design: Patients with type 2 diabetes mellitus (T2D) have an increased fracture risk despite a normal or elevated bone mineral density (BMD). The aim of this cross-sectional in vivo study was to assess parameters of peripheral bone microarchitecture, estimated bone strength and bone remodeling in T2D patients with and without diabetic microvascular disease (MVDC and MVDK respectively) and to compare them with healthy controls. Methods: Fifty-one T2D patients (MVDC group: nZ25) were recruited fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(130 citation statements)
references
References 38 publications
7
116
2
5
Order By: Relevance
“…In agreement with Patsch et al, we report that women with fracture had higher porosity than those without fracture, while women with T2DM had lower porosity than nondiabetic women. Moreover, cortical porosity is suggested to be increased only in T2DM patients with microvascular complications, however, one limitation in that study was that fracture status was not taken into account [34]. They reported no correlation between bone structure and duration of disease, which is in agreement with our findings of a non-significant association between cortical porosity and diabetes duration.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In agreement with Patsch et al, we report that women with fracture had higher porosity than those without fracture, while women with T2DM had lower porosity than nondiabetic women. Moreover, cortical porosity is suggested to be increased only in T2DM patients with microvascular complications, however, one limitation in that study was that fracture status was not taken into account [34]. They reported no correlation between bone structure and duration of disease, which is in agreement with our findings of a non-significant association between cortical porosity and diabetes duration.…”
Section: Discussionsupporting
confidence: 84%
“…These data suggest a tendency towards increased cortical porosity of the distal radius in women with T2DM in studies with limited number of participants using HR-pQCT. However, the absolute differences in cortical porosity between those with and without T2DM were small, and the cortical thickness was below 1 mm at the distal radius [11][12][13]34]. Moreover, HR-pQCT present low values of porosity (1-15%) because of quantifying only porosity of the compact cortices and only pores over 100 µm in diameter, and the threshold based segmentation may misclassify trabecularised cortical bone as trabecular bone [23,24,26,32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MRI studies revealed greater cortical porosity in individuals with T2DM compared with nondiabetic controls, 61,62 a finding repeated by a study using quantitative CT (Xtreme-CT), especially in those with fractures and/or microvascular complications. [6][7][8][9] Recent diagnostic advances enable the measurement of in vivo bone material strength (BMS) by the minimally invasive, bone microindentation testing. 7,63 Postmenopausal women with T2DM demonstrated lower BMS and greater radial cortical porosity.…”
Section: T2dmmentioning
confidence: 99%
“…The presence of microvascular complications in DM have also been associated with reduction of BMD in T1DM 5 and with bone micro-architectural abnormalities in T2DM. [6][7][8][9] Increasing evidence shows the interaction between plasma glucose levels and bone metabolism, revealing mechanisms through which bone fragility may develop in DM. Whether this interaction translates into increased risk for fragility fractures and decreased BMD in all DM populations remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There is decreased cortical thickness and volumetric BMD (vBMD), with increased cortical porosity and pore size in T2DM [44] patients with microvascular disease (retinopathy, neuropathy or nephropathy). These changes are associated with decreased bone strength by finite element analysis [44,45] and are greater in T2DM patients with previous fractures [46], suggesting that they may be clinically significant contributors to fracture risk.…”
Section: Type 2 Diabetes Fracture and Bmdmentioning
confidence: 99%